Classification of Low-Income Countries for the Purpose of Debt Limits in Fund-Supported Programs : 2011 Update. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
This short paper informs the Executive Board of staff's assessment of macroeconomic and public financial management capacity (henceforth 'capacity') in PRGT-eligible countries (henceforth 'low-income countries') with Fund-supported programs for the purpose of setting debt limits. Capacity plays an important role in the framework for debt limits. This framework includes a menu of options for concessionality requirements to reflect the diversity of situations in low-income countries (LICs). Eligibility for a particular option is related to an assessment of debt vulnerabilities and capacity.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Countries Eligibility; Country; Debt Limit; PP; Vulnerability Assessment; Burkina Faso